The Eighth Sustainable Development Goal considering the economic system and its contradictions – A Critique - José António de Sousa Pinho (Jurnal Sentris, 2020)
This article focuses on the eighth Sustainable Development Goal (SDG) for the global community, analysing its objectives and recommendations that are to be achieved by 2030 in the sectors of economic growth and employment. It is a critique of the SDG chosen, in light of the current economic system and its contradictions, taking into account the new factors of the decade, such as technology and the environmental crisis. Economic growth was present in every economic analysis in the past decade, but should it be the focus of the next? The current environmental concerns have forced the global community to rethink the way we look at economic growth and the system in general. The article will also explore the contradictions in employment and work while attempting to explain the problems of this sector. A special attention will be given to profit and the way it prevents the creation of decent jobs. The new possibilities of the green economy and the technological progress will be taken into account and developed. It will finish with a reflection on the economic system in general and the SDGs, while also proposing a solution to the problems of the next decades concerning the economic and employment sector.